State-of-the-art catechol porphyrin COF catalyst for chemical fixation of carbon dioxide via cyclic carbonates and oxazolidinones - Saptal, Vitthal; Shinde, Digambar Balaji; Banerjee, Rahul; Bhanage, Bhalchandra M. (Catalysis Science & Technology, 2016)
A highly porous, crystalline catechol porphyrin COF was synthesized and applied as an organocatalyst for the chemical fixation of carbon dioxide to synthesize value-added chemicals such as cyclic carbonates and oxazolidinones under solvent-free and transition-metal-free conditions. The high surface area and the functionalities of the COF catalyst act synergistically to activate the starting material. The 2,3-DhaTph shows excellent activity towards cyclic carbonates at the atmospheric pressure of carbon dioxide. Additionally, this catalytic system is recyclable in nature and provides a higher turnover number than previously reported organocatalysts.